2016
DOI: 10.4103/0301-4738.185592
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in diagnosis and management of Mycotic Keratitis

Abstract: Mycotic keratitis is a major cause of corneal blindness, especially in tropical and subtropical countries. The prognosis is markedly worse compared to bacterial keratitis. Delayed diagnosis and scarcity of effective antifungal agents are the major factors for poor outcome. Over the last decade, considerable progress has been made to rapidly diagnose cases with mycotic keratitis and increase the efficacy of treatment. This review article discusses the recent advances in diagnosis and management of mycotic kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 94 publications
(181 reference statements)
1
61
0
2
Order By: Relevance
“…Similar to CF cases, the use of polymyxin antibiotics can improve the poor prognosis of fungal keratitis, due to the emergence of MDR fungal pathogens, particularly Fusarium spp. [36], and to the limited ocular penetration of antifungals [37]. Notably, PMB can be formulated for ophthalmic use [16], which is described as a highly effective drug on bacterial corneal ulcerations [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CF cases, the use of polymyxin antibiotics can improve the poor prognosis of fungal keratitis, due to the emergence of MDR fungal pathogens, particularly Fusarium spp. [36], and to the limited ocular penetration of antifungals [37]. Notably, PMB can be formulated for ophthalmic use [16], which is described as a highly effective drug on bacterial corneal ulcerations [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also observed highly diverse pathogens. In addition to well-established infectious agents such as Alternaria, Bipolaris, Curvularia, and Penicillium , 25 , 26 rarely reported species included Corynespora, 27 Lasiodiplodia, 28 Scedosporium apiospermum, 29 Scedosporium, 26 Sarocladium, 30 and Scopulariopsis brevicaulis. 31 Moreover, Paracremonium and Phellinus , which have never been reported as pathogens of human keratitis, have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Во фрагментах всех 6 удаленных роговиц и в 2 исследованных соскобах с роговицы обнаружена ДНК Fungi и не обнаружена ДНК Candida albicans. Рост плесневых грибков (Аspergillius spp) на агаре Сабуро и отрицательные результаты ПЦР на Candida albicans согласуются с современными представлениями о ведущей роли нитчатых грибов, а не Сandida аlbicans, в этиологии кератомикозов у носителей контактных линз, в отличие от пациентов с предшествующими заболеваниями глазной поверхности, у которых кератиты обусловлены в основном Сandida аlbicans [4,6,7,12]. У 2 пациентов в удаленной при кератопластике роговице, помимо ДНК Fungi, обнаружена ДНК ВЭБ, а еще у одного -ДНК ВЭБ и ДНК ЦМВ.…”
Section: Discussionunclassified
“…Keywords: fungal corneal ulcers, laboratory diagnostics, PCR чувствительностью [6][7][8][11][12][13]. Однако многообразие видов патогенных грибов и отсутствие тест-систем для выявления многих из них ограничивают возможности ПЦР.…”
Section: Introductionunclassified